2022
DOI: 10.3389/fpls.2022.1006720
|View full text |Cite
|
Sign up to set email alerts
|

Maize/soybean strip intercropping produces higher crop yields and saves water under semi-arid conditions

Abstract: Sustainable increases in crop production require efficient use of resources, and intercropping can improve water use efficiency and land productivity at reduced inputs. Thus, in a three-year field experiment, the performance of maize/soybean strip intercropping system differing with maize plant density (6 maize plants m-2, low, D1; 8 maize plants m-2, medium, D2; and 10 maize plants m-2, high, D3) was evaluated in comparison with sole maize or soybean cropping system. Results revealed that among all intercropp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…In previous maize-soybean intercropping study it was found that intercropping significantly improves N content, N uptake and N use efficiency of maize crop particularly under optimized N fertilization, mainly because of the underlying rhizosphere modification and nutrient facilitation provided by soybean ( Yong et al., 2018 ). In another maize-soybean intercropping study it was reported that the significant N transfer from soybean to maize improved the NUE of maize when treated with optimal N fertilization ( Zhang et al., 2017b ; Raza et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous maize-soybean intercropping study it was found that intercropping significantly improves N content, N uptake and N use efficiency of maize crop particularly under optimized N fertilization, mainly because of the underlying rhizosphere modification and nutrient facilitation provided by soybean ( Yong et al., 2018 ). In another maize-soybean intercropping study it was reported that the significant N transfer from soybean to maize improved the NUE of maize when treated with optimal N fertilization ( Zhang et al., 2017b ; Raza et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, these indices were more evident under N 1 treatment than N 0 and N 2 . Possibly, this could due to the better utilization of the available natural resources such as land, light, water, and nutrients ( Nasar et al., 2020b ; Raza et al., 2020 ; Raza et al., 2022 ), or could be due to the N fertilization, which is an important element required for plant growth and development ( Zhang et al., 2014 ; Nduwimana et al., 2020 ). Moreover, legume in intercropping with cereal are also known to improve the N status of cereal crop by facilitative transfer of N to their corresponding cereal crop through the underlying facilitative root interactions, which ultimately leads to an increase yield production of intercropping cereals than mono-cropping ( Shao et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data from field experiments of super‐high‐yield soybean cultivation in Xinjiang province, China and from other high‐yield production systems, indicate that high‐density planting shows promise for achieving higher soybean yields (Liu et al, 2020d). Maize–soybean intercropping allows the harvest of an extra season of soybean seeds with only slight to no reduction in the yield of maize and has been practiced on a large scale around the world (Du et al, 2018; Hussain et al, 2020; Pelech et al, 2022; Raza et al, 2022). However, both high‐density planting and maize–soybean intercropping share some common and specific challenges.…”
Section: Challenges and Future Prospectivesmentioning
confidence: 99%
“…Due to global warming, precipitation rates are anticipated to lessen in Kenya with a forecast increase in evapotranspiration levels (Nyawade et al, 2021). Such changes would result in a decrease in available soil moisture and increased SOM decomposition, mostly close to the soil surface thus affecting soil water retention and carbon sequestration (Raza et al, 2021, 2022; Seleiman et al, 2021). Regarding agricultural intensification, the use of ISFM strategies to manage low nutrient holding capacity is long overdue in tropical and subtropical soils due to high SOM turnover.…”
Section: Introductionmentioning
confidence: 99%
“…Due to global warming, precipitation rates are anticipated to lessen in Kenya with a forecast increase in evapotranspiration levels (Nyawade et al, 2021). Such changes would result in a decrease in available soil moisture and increased SOM decomposition, mostly close to the soil surface thus affecting soil water retention and carbon sequestration (Raza et al, 2021(Raza et al, , 2022Seleiman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%